1993
DOI: 10.1007/bf00369454
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease with involvement of the parasympathetic ganglia

Abstract: We report the distribution of Lewy bodies in an 83-year-old man who was diagnosed histopathologically as having Parkinson's disease. Many sections were taken from the brain, spinal cord, spinal dorsal root ganglia and peripheral autonomic systems. In the central nervous system, Lewy bodies were present in many of the areas already reported by previous authors. In the peripheral nervous system, Lewy bodies were present in the sympathetic ganglia, enteric nervous system of the alimentary tract and the submandibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 8 publications
1
40
0
1
Order By: Relevance
“…It has been suggested, for example, that olfactory dysfunction, depression and autonomic nervous system dysfunction may be predictive for subsequent PD [3,22,29]. Olfactory bulb and peripheral autonomic nervous system synucleinopathy, are very common if not universal findings in PD [10][11][12]14,37,39,46,48,49]. Olfactory dysfunction and olfactory bulb synucleinopathy have been reported to be present in ILBD cases and hence smell tests and/or olfactory bulb biopsy may be useful for early diagnosis in PD and/or DLB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested, for example, that olfactory dysfunction, depression and autonomic nervous system dysfunction may be predictive for subsequent PD [3,22,29]. Olfactory bulb and peripheral autonomic nervous system synucleinopathy, are very common if not universal findings in PD [10][11][12]14,37,39,46,48,49]. Olfactory dysfunction and olfactory bulb synucleinopathy have been reported to be present in ILBD cases and hence smell tests and/or olfactory bulb biopsy may be useful for early diagnosis in PD and/or DLB.…”
Section: Resultsmentioning
confidence: 99%
“…The differences between studies may be due to differing immunohistochemical methods, differing subject ages and differing sampling sites. Although Parkinson's disease (PD) is generally considered a disease of the central nervous system (CNS), it has long been known that Lewy bodies may also be found in the peripheral autonomic nervous system in PD subjects [15,18,36,37,46,49]. Recent studies using immunohistochemical staining for α-synuclein have found that the peripheral autonomic nervous system is a common site of affectation in ILBD.…”
Section: Introductionmentioning
confidence: 99%
“…Cite this article as Cold Spring Harb Perspect Biol 2016;8:a023630 purple) (Bloch et al 2006;Braak et al 2006;Braak and Del Tredici 2009;Del Tredici et al 2010; see also den Hartog Jager and Bethlem 1960; Wakabayashi et al 1988Wakabayashi et al , 1989Wakabayashi et al , 1990Wakabayashi et al , 1993Takeda et al 1993;Wakabayashi and Takahashi 1997a,b;Cersó simo et al 2011;Beach et al 2013;Adler et al 2014). The brain is closely connected with postganglionic ENS neurons via axons of the preganglionic parasympathetic motor neurons of the dmX.…”
Section: Tau and A-synuclein Dissemination In Ad And Pdmentioning
confidence: 99%
“…(Legend continues on following page.) 1960;Wakabayashi et al 1988Wakabayashi et al , 1989Wakabayashi et al , 1990Wakabayashi et al , 1993Takeda et al 1993; Wakabayashi and Takahashi 1997a,b; Cersó simo et al 2011;Beach et al 2013; Adler et al 2014). The brain is closely connected with postganglionic ENS neurons via axons of the preganglionic parasympathetic motor neurons of the dmX.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] In some PD and dementia with Lewy bodies patients, Lewy pathology is present in the peripheral vagal nerve and ganglia. 10,11 These axons originate in the DMV. There are reports of strong Lewy pathology in the DMV preganglionic parasympathetic neurons of nearly all PD patients studied (see below).…”
Section: Introductionmentioning
confidence: 99%